Lifestyle Migration and the Quest for a Life-long Vacation - IBRAHIM, Zainub; TREMBLAY, Rémy (Téoros)

(untitled) (Université du Québec à Montréal, 2017)
With international migration on the rise, researchers are interested in understanding the link between migration and tourism more than ever before. In this paper, we introduce some of the main concepts used in studies on migration and tourism, which lead to our discussion of lifestyle migration. We then examine the case of the Québécois in Florida in light of the literature on lifestyle migration and assess whether this case fits the definition and characteristics of lifestyle migration. Our analysis is based on semi-structured in-depth interviews with thirty Québécois migrants in Florida. We find that even though our case study does not adhere to the classical definition of lifestyle migration as it does not meet the restriction of relative affluence, it is representative of the characteristics of this type of migration, and class issues play a significant role in the lives and experiences of the migrants.